Mindset : the new psychology of success - Dweck, Carol S., 1946- (New York : Ballantine Books, 2017)
Reveals how personal mindsets affect and control every aspect of one's life and offers advice on how to promote success and personal fulfillment.
The mindsets -- Inside the mindsets -- The truth about ability and accomplishment -- The mindset of a champion -- Mindset and leadership -- Mindsets in love (or not) -- Parents, teachers, and coaches : where do mindsets come from? -- Changing mindsets.
Includes bibliographical references (p. [247]-268) and index.
Choice
Library Journal Starred
Publisher's Weekly
Choice, December 2006
Library Journal Starred, February 2006
Keywords: Belief and doubt; Success -- Psychological aspects; Belief and doubt; Success -- Psychological aspects